The Effect of Organizing Sewing Training on Women's Economic Independence in The Kursu Korsa Institution - Maghfiroh, Leny Lailatul; Wahyuni, Sri; Rahma, Rezka Arina (Universitas Negeri Malang, 2024)
Research objectives: (1) to analyze the effect of organizing sewing training on increasing women's economic independence at Korsa course institutions, (2) to measure how much increase in women's economic independence can be achieved through sewing training at Korsa course institutions, (3) to determine the effect of sewing training on women's economic independence at Korsa course institutions. The research results show that (1) there is a significant influence between the implementation of sewing training in increasing women's economic independence, (2) there is an increase of 63.3% in the process of women's economic independence, which means that the implementation of sewing training on women's economic independence has greatly increased, (3) The results of the analysis show that the regression coefficient between sewing training and economic independence is -2.451, with a significance level of 0.017. There is an influence of sewing training on women's economic independence in terms of self-development, potential, creativity, communication and negotiation. Keywords : Training Institute, Sewing Training, Women's Economic Independence